Impact of Clinical Information on Lumbar Spine MRI Evaluation of Patients Suspected of Lumbar Disk Herniation - Sattam S. Lingawi (Journal of King Abdulaziz University: Medical Sciences, 2023)
To assess the impact of clinical information on Magnetic Resonance Imaging evaluation of lumbar spine in patients suspected of lumbar disk herniation. Lumbar spine MRI of 50 consecutive patients with back pain and 50 normal volunteers were assessed for the presence or absence of a disk bulge or herniation. The assessment included four disk levels in each MR study (L2-3, L3-4, L4-5 & L5-S1). All images were assessed before and after disclosure of clinical information. Without clinical information: 148 normal levels, 48 disk bulges and 4 disk herniations were detected in the volunteer group as compared to 20 normal levels, 108 disk bulges and 72 disk herniations in the patient group. With clinical information: 132 normal levels, 64 disk bulges and 4 disk herniations were reported in the volunteer group as compared to 12 normal levels, 112 disk bulges and 76 disk herniation in the patient group. Clinical information disclosure resulted in 33% increase in the reported number of bulging disks in volunteers, and 5.5% increase in the reported number of herniation in patients. Clinical information disclosure does not influence the detection of herniations, but lowers the threshold for reporting bulging disks.